Penyuluhan Strategi Pengelolaan Bisnis Di Era New Normal - Maria Septijantini Alie (Jurnal Pengabdian Kepada Masyarakat, 2023)
AbstractThe Covid-19 pandemic has hit many countries, including Indonesia. Covid-19 has had an impact on various sectors including Micro, Small and Medium Enterprises, including a decrease in the number of sales. The normal era now brings change to society. Community Service Activities are carried out to provide counseling on business management strategies in the new normal era. By using and managing digital media, it is hoped that business actors will be able to determine the right type of digital media for the products being marketed. The material for this activity is strategies for using and managing digital media, optimizing digital marketing and product branding to increase the ability to create attractive content, promotion as well as as an alternative media for business actors in the service sector. The results of the activities have a positive impact on business actors by increasing knowledge about digital media, increasing knowledge of various media that can be used and increasing skills in using and managing business.  Keyword: Business Management, MSME, Digital Marketing. AbstrakPandemi Covid-19 telah melanda banyak negara, termasuk Indonesia. Covid-19 telah menimbulkan dampak di berbagai sektor termasuk Usaha Mikro Kecil dan Menengah diantaranya yakni turunnya jumlah penjualan. Era now normal membawa perubahan kepada masyarkat.  Kegiatan Pengabdian Pada Masyarakat dilakukan untuk memberikan penyuluhan tentang strategi pengelolaan bisnis di era new normal. Dengan menggunakan dan mengelola media digital, diharapkan para pelaku usaha dapat menentukan jenis media digital yang tepat untuk produk yang dipasarkan, Materi kegiatan berupa ini adalah strategi  penggunaan dan pengelolaan media digital, optimalisasi digital marketing serta branding produk untuk meningkatkan kemampuan pembuatan konten yang menarik, promosi serta sebagai media alternatif bagi pelaku usaha bidang jasa. Hasil kegiatan memberikan dampak positif bagi para pelaku usaha dengan adanyapeningkatan pengetahuan tentang media digital, peningkatan pengetahuan berbagai media yang dapat digunakan dan adanya peningkatan keterampilan dalam penggunaan dan  pengelolaan usaha. Kata Kunci:  Pengelolaan Bisnis, UMKM,  Pemasaran Digital.